1997
DOI: 10.1177/073168449701600806
|View full text |Cite
|
Sign up to set email alerts
|

Short Banana Fiber Reinforced Polyester Composites: Mechanical, Failure and Aging Characteristics

Abstract: This paper describes the tensile, impact, flexural properties and aging behavior of short banana fiber reinforced polyester composites with special reference to the effect of fiber length and fiber content. Maximum tensile strength was observed at 30 mm fiber length while impact strength gave the maximum value for 40 mm fiber length. Incorporation of 40% untreated fibers gave a 20% increase in the tensile strength and a 341% increase in impact strength. On treatment with silane coupling agent, composites showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(138 citation statements)
references
References 19 publications
13
122
0
3
Order By: Relevance
“…Otro aspecto a resaltar es que usualmente las bajas proporciones de fibra en el MC, están asociadas a un pobre comportamiento mecánico (Pothan, et al, 1997). Sin embargo, y a pesar de que en este trabajo fue utilizado el modo de fabricación por moldeo manual, que no permite contenidos de fibra por encima del 14-15% (Dittenber, et al, 2012), se lograron mejoras sensibles en las propiedades mecánicas de los MC respecto de las que se observaron en los especímenes sin tratar.…”
Section: Prueba De Tensiónunclassified
“…Otro aspecto a resaltar es que usualmente las bajas proporciones de fibra en el MC, están asociadas a un pobre comportamiento mecánico (Pothan, et al, 1997). Sin embargo, y a pesar de que en este trabajo fue utilizado el modo de fabricación por moldeo manual, que no permite contenidos de fibra por encima del 14-15% (Dittenber, et al, 2012), se lograron mejoras sensibles en las propiedades mecánicas de los MC respecto de las que se observaron en los especímenes sin tratar.…”
Section: Prueba De Tensiónunclassified
“…9). Our earlier studies indicated that the acceptor number, which is indicative of the electron accepting ability, is found highest for bres treated with the silane A151 [10]. The E T (30) parameter which is indicative of the overall polarity is also found to be maximum for bres treated with the silane A151.…”
Section: Silane A151 (Vinyl Triethoxysilane)mentioning
confidence: 99%
“…Table 1 contains the mechanical properties of banana bres of various diameters. This bre was also found to be an effective reinforcement in polyester [10]. Treatment with silane A151 (vinyl triethoxysilane) proved to be effective in increasing the tensile properties of the composite in our earlier studies [9].…”
Section: Introductionmentioning
confidence: 99%
“…Different natural fibers such as jute, coir, banana, straw, palm, and others have been previously investigated to be used as natural reinforcements in composites [5][6][7][8][9]. Moreover, natural fibers were used as natural hybrids by a proper combination of natural reinforcements, that is, hybridization as reported in [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%